Defining crimes: essays on the special part of the criminal law - Duff, Antony ([Oxford monographs on criminal law and criminal justice], 2005)
Introduction : the special part and its problems / R.A. Duff and Stuart P. Green -- The classification of crimes and the special part of the criminal law / Jeremy Horder -- Criminalizing endangerment / R.A. Duff -- Malum prohibitum and retributivism / Douglas Husak -- The possession paradigm : the special part and the police power model of the criminal process / Markus Dirk Dubber -- The distinctiveness of domestic violence : a freedom-based account / Victor Tadros -- What's wrong with bribery / Stuart P. Green -- On the nature and rationale of property offences / A.P. Simester and G.R. Sullivan -- Is strict liability rape defensible? / Kyron Huigens -- Merger and felony murder / Claire Finkelstein.